Advances in Automation System for Agricultural Irrigation System - Husainy, Avesahemad SN (Journal of Advanced Research in Mechanical Engineering and Technology, 2022)
Fertigation is most important in agriculture due to the growth of crops, and their yields depend upon it. If the ratio of fertilizer and water is either higher or lower, it produces various crises. In today’s growing technology and automation, many feasible ways can be used efficiently and anywhere with proper access. With the help of a microcontroller unit, various automatic systems like IoT, PLC system, proportional-integral-derivative, and PID with a fuzzy algorithm, the fertigation system has been implemented. With the help of sensors, this system can detect the soil moisture and water level and stops the water supply. The time can be scheduled as per the choice of the user. This system will ease the farmers to work efficiently, and more time is reduced than the time needed for human interference. How to cite this article: Patil PK, Takawade SJ, Patil KN et al. Advances in Automation System for Agricultural Irrigation System. J Adv Res Mech Engi Tech 2022; 9(1&2): 18-23. DOI: https://doi.org/10.24321/2454.8650.202201